Pengaruh Literasi Keuangan Syariah, Sosialisasi, Dan Jenis Kelamin Terhadap Keputusan Menggunakan Produk Perbankan Syariah Pada Generasi Z Di Jambi - Ferawati, Rofiqoh; Bariatun, Linda (Manajemen Keuangan Syariah, 2025)
This study aims to determine the effect of Islamic financial literacy, socialization, and gender on the decision to use Islamic banking products on generation z in Jambi. The method used in this study is a quantitative method, using SPSS 29. The sample in this study was 100 samples of generation z in Jambi, by distributing questionnaires. The results of the study showed that Islamic financial literacy had a significant effect on the decision to use Islamic banking products as evidenced by a sig value of 0.001 < 0.05. Socialization had a significant effect on the decision to use Islamic banking products as evidenced by a sig value of 0.001 <0.05. Gender did not have a significant effect on the decision to use Islamic banking products as evidenced by a sig value of 0.505 > 0.05. Sharia financial literacy, socialization and gender simultaneously have a significant effect on the decision to use sharia banking products, of 0.620 or 62%.